The global impact of public and private funding on cultural and economic movie success: evidence from German film funding - Nicolas R. Weber; André Marchand; Reinhard E. Kunz (Journal of Cultural Economics, 2023)
Entertainment products such as movies are risky investments but contribute to societal welfare through their cultural and economic value. Therefore, movie production receives financial support from both private investors and public institutions, in the form of subsidies. Noting the ongoing debate about the actual impact of such funding, in research and practice, this study reviews a large sample of 1984 movies (co-) produced in Germany and released to cinemas over a 10-year period. The findings demonstrate the positive impact of public funding on movie success: indirectly by attracting private funding, and directly by increasing local and global box office revenues. However, public funding does not directly improve movie quality, which contradicts one of the aims of public funding. The analyses reveal different correlations and interaction effects with regard to financing and quality signals generated by the cast, directors, and producers of movies. Public funding emerges not only as relevant for the economic success of movies but also as a factor that supports their cultural contribution.
Keywords: 330; Movie success; Film financing; Signaling; Public subsidization; Private investment